Consumo foliar da traça-das-crucíferas em couve e brócolis tratados com sinigrina - Bortoli, Sergio Antonio De (2014)
Leaf area estimation, based on their reduction due to consumption by phytophagous insects, is a basic methodology in several areas of Entomology, for instance, in studies about plant resistance, economic entomology and nutritional ecology. One of the factors that can affect the amount of leaf area consumed by insects is the presence of certain chemicals in the leaves, such as sinigrin in Brassicaceae. Thus, several concentrations of sinigrin were applied on the leaves of cabbage and broccoli (0.2, 0.4, 0.8, 1.6, and 3.2 mg/mL in 5% Tween20(r) solution) in order to measure leaf area consumption by larvae of P. xylostella, estimated by the percentage of area reduction, weight loss and visual scale of notes. The results show that the concentrations of 0.2, 0.4 and 3.2 mg/mL of sinigrin increase larvae consumption of P. xylostella on kale leaves and decrease it on broccoli leaves. The methodologies used provide similar results, and fresh weight measurements and visual grades are more practical.